The Filth and the Fury: An Essay on Punk Rock Heavy Metal Karaoke - Jason Lee Oakes (Current Musicology, 2008)
Musical voices cross and enunciate thresholds. Along these lines, I have attempted to map some of the thresholds that are crossed and enunciated by singers and other participants at PMK. These thresholds are diverse, with boundaries negotiated between and around musical genres, gender roles, ontological notions of subjectivity, and shifting geographic significances in New York City. To examine these boundary negotiations, I chose abjection as an interpretive frame for a number of reasons. First, the event is grounded in two performative lexicons- the genre of punk and the practice of karaoke- that are already discursively situated in terms of the abject. Also, given that abjection, as theorized by Kristeva, is centrally concerned with the body, and especially with horrific and sexualized experiences with the body, it provides a useful lens for analyzing the vocal and bodily display, and the bawdy humor and horrific imagery, found in abundance at PMK. Finally, and most importantly, the regular participants utilize the terms of the abject in their own speech and in their own interpretations of the event.